Personality changes during antidepressant treatment - Hruby, Radovan (Array, 2009)
We have investigated the changes of Temperament and Character Inventory (TCI) dimensions of personality in outpatients during 6 months of antidepressant treatment. 30 outpatients were treated for mild or moderate depressive episode, current mild or moderate episode of reccurent depressive disorder or mixed anxiety and depressive disorder (ICD-10). The intensity of depression was assessed by the Montgomery-Asberg Depression Rating Scale (MADRS) at the beginning of treatment and then after the 1st, 3rd and 6th month of treatment. The TCI dimensions were assessed by the Temperament and Character Inventory-Revised (TCI-R) at the same time periods as the MADRS. The mean scores of the TCI-R dimensions and MADRS were processed by Wilcoxon pair test